ANALISIS EKONOMI DAN PROSPEK USAHA TANAMAN DAN TERNAK SAPI DI LAHAN PERKEBUNAN KELAPA - S. Rusdiana; Cut R Adawiyah (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2013)
This  paper  studies  the  results  of  the  2012  field  survey  research  area targeted  is  the  location  of  plantations  owned  by  farmers  in  the  village  of  Coventry District Leuwi Booths Bogor Regency of West Java, to get  a general idea on the land through a pattern of oil palm plantations and the business of cattle through research studies with application of livestock on land that has not produced oil crops (TBM), coconut trees that produce (TM) and coconut trees that do  not produce or damaged (TTM  /  TR)  conservation-minded,  analissi  financial  economics.  Financial  analysis methods  is  used  to  determine  income  from  coconut  plantations  and  cattle  business. Primary data  were obtained directly from the farmers, the secondary data obtained from  the  relevant  authorities  and  research  results.  Primary  and  secondary  data collected are tabulated qualitative and quantitative analysis as well as the tables. The results  of  the  financial analysis  of the  plant  economically  immature  coconut  (TBM) gains  from  the  coconut  around  Rp-3.780.000/tahun/ha  because  immature  coconuts, which  means  the  cost  is  still  in  pemeliharana  coconut  plants,  of  cattle  around Rp5.143.000  /  year,  whereas  immature  (TBM)  benefits  of  coconut  around Rp6.750.000 / year / ha of cattle around Rp1.972.000/tahun and plants do not produce or  damaged  plants  (TTM  /  TR)  gains  from  the  coconut  around  Rp1.200.000  of livestock  around  Rp4.950.000/tahun.  It  means  that  utilization  of  vacant  land  in coconut plantations  damaged by cattle in financial analysis and profitable livestock farmers can maintain the existence of livestock.